2014
DOI: 10.1093/cid/ciu010
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Antimicrobial Therapy for Asymptomatic Bacteriuria Among Noncatheterized Inpatients: A Proof-of-Concept Study

Abstract: This proof-of-concept study demonstrates that no longer routinely reporting urine culture results from noncatheterized medical and surgical inpatients can greatly reduce unnecessary antimicrobial therapy for asymptomatic bacteriuria without significant additional laboratory workload. Larger studies are needed to confirm the generalizability, safety, and sustainability of this model of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
150
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(155 citation statements)
references
References 10 publications
4
150
1
Order By: Relevance
“…During the intervention period, rather than routinely reporting positive urine cultures from noncatheterized inpatients, technicians appended a comment to electronic medical records to request clinicians to call the laboratory for culture results if UTI is strongly suspected. Of the 37 modified reports, results were requested for only 5 (14%) patients, decreasing the rate of antibiotic therapy from 48% to 12% in noncatheterized patients with ASB (12).…”
Section: Counterpointmentioning
confidence: 99%
See 1 more Smart Citation
“…During the intervention period, rather than routinely reporting positive urine cultures from noncatheterized inpatients, technicians appended a comment to electronic medical records to request clinicians to call the laboratory for culture results if UTI is strongly suspected. Of the 37 modified reports, results were requested for only 5 (14%) patients, decreasing the rate of antibiotic therapy from 48% to 12% in noncatheterized patients with ASB (12).…”
Section: Counterpointmentioning
confidence: 99%
“…A study in the Netherlands of 1993 nonpregnant women with symptoms consistent with a UTI demonstrated that 94% with a nitrite-positive specimen and 71% with a positive LE result received antimicrobial therapy but that only 20% of those with negative results for these tests were prescribed antibiotics (11). Similarly, a Canadian study of 231 women with symptoms of a UTI demonstrated that evaluation for pyuria would reduce the frequency of unnecessary antimicrobial prescription by one-third (12).…”
mentioning
confidence: 99%
“…This problem may require a slightly different strategy to address. For example, in a prospective before-and-after proof-ofconcept study, nonreporting of urine culture and susceptibility results for noncatheterized medical and surgical inpatients resulted in a significantly reduced rate of ASB treatment (16). This more aggressive variant of selective reporting will likely be further validated in future studies and may have a substantial impact on overutilization in many settings.…”
Section: Discussionmentioning
confidence: 99%
“…Since AMR may emerge in bacteria as a response to selective antimicrobial pressure (i.e., when bacteria is in the presence of an antimicrobial drug), there is a potential risk that fewer and fewer antimicrobials will remain effective in the future. Unnecessary antibiotic treatment has been shown to account for a substantial burden of inappropriate antimicrobial use in Canada (1)(2)(3)(4). Due to growing concern about the link between antimicrobial usage (AMU) and AMR, a shift towards more prudent use of antimicrobials has been one of the areas emphasized in combatting the spread of AMR (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%